2019
DOI: 10.3390/ijms21010233
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Dynamic Transcriptome Landscape of Leaf, Bract, and Lupulin Gland in Hop (Humulus lupulus L.)

Abstract: The hop plant (Humulus lupulus L.) produces several valuable secondary metabolites, such as prenylflavonoid, bitter acids, and essential oils. These compounds are biosynthesized in glandular trichomes (lupulin glands) endowed with pharmacological properties and widely implicated in the beer brewing industry. The present study is an attempt to generate exhaustive information of transcriptome dynamics and gene regulatory mechanisms involved in biosynthesis and regulation of these compounds, developmental changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
5
18
0
Order By: Relevance
“…There is increasing interest among growers and industry partners to better understand the response of hops to HT and LW stress, and to breed varieties with improved tolerance to abiotic stress. There are a number of genomic resources now available to assist breeding for H. lupulus, including the genome sequence 40,47,48 , a proteome 49 , and transcriptomes 13,14 . This study adds the transcriptome sequence under a combination of HT stress and LW stress, as well as a transcriptome from hop root tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing interest among growers and industry partners to better understand the response of hops to HT and LW stress, and to breed varieties with improved tolerance to abiotic stress. There are a number of genomic resources now available to assist breeding for H. lupulus, including the genome sequence 40,47,48 , a proteome 49 , and transcriptomes 13,14 . This study adds the transcriptome sequence under a combination of HT stress and LW stress, as well as a transcriptome from hop root tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used leaf and stem tissue and www.nature.com/scientificreports/ their associated lupulin glands as proxies for cone lupulin glands. The bitter acids are found in leaf tissue in small amounts 12,13 . Clark et al 14 and Mishra et al 13 found many genes for the bitter acid pathway expressed in leaf tissue, though some, including VPS and BCAT2, have higher expression in lupulin glands extracted from cones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichome differentiation mechanisms have been investigated in Arabidopsis thaliana , with transcription factor (TFs) groups playing key roles in the transcriptional networks for trichome production and patterns ( Tian et al, 2017 ). While genomic studies are available for other economic plants, including Humulus lupulus which belongs to the Cannabaceae family ( Matoušek et al, 2016 ; Mishra et al, 2020 ), similar studies for cannabis are lacking despite their potentially important impacts for precise cannabis trichome control. Taking advantage of the genetic libraries available for related species with similar resin secretions will help guide these much-need studies ( Braich et al, 2019 ; Zager et al, 2019 ; Liu et al, 2021 ).…”
Section: Trichome Profilesmentioning
confidence: 99%
“…Hop ( Humulus lupulus L.) is a diploid, dioecious, perennial climbing plant belonging to the Cannabaceae family. Female plants are cultivated for the commercial production of inflorescences (cones), which are mainly used in the brewing industry but also commonly used in the production of pharmaceuticals and cosmetics [ 1 ]. In cones, flavour-active secondary metabolites are biosynthesized and accumulate in glandular trichomes and lupulin glands.…”
Section: Introductionmentioning
confidence: 99%